KEBIASAAN MAKANAN DAN PERUBAHAN ONTOGENETIK MAKANAN IKAN BAJI-BAJI (Grammoplites scaber) DI PANTAI MAYANGAN, JAWA BARAT [Food habits and ontogenetic changes in the diet of the rough flathead Grammoplites scaber in Mayangan Coast, West Java] - Charles P.H. Simanjuntak; Ahmad Zahid (Jurnal Iktiologi Indonesia, 2009)
The study on the food habits and ontogenetic changes in the diet of the rough flathead, Grammoplites scaber, in Mayangan Coast, West Java, was conducted in 12 months. The main objectives of the study were to analyze the food compotition and the changes of the food in relation to season and fish length. Samplings were done once in a month, using gillnet and beach seine. Total samples were 795 individuals and the range of total length was between 107-364 mm. Food analysis was determined by using index of preponderance. The result showed that the food of the rough flathead fish could be grouped into four groups. The groups are crustacea, pisces, cephalopod, and bivalve. This fish was crustacivore and the major foods were Portunus, Metapenaeus dan Penaeus. The main foods which were consumed varied each month. Along with the increasing of the fish size, there was a change of the main foods. Smaller fish tend to consume Penaeus; whereas the larger one tends to consume Portunus, Metapenaues and Saurida.